Serum Calcitonin-Negative Medullary Thyroid Carcinoma: A Case Series of 19 Patients in a Single Center - Kim, Sun Jung; Yun, Hyeok Jun; Shin, Su-Jin; Lee, Yong Sang; Chang, Hang-Seok (Frontiers in Endocrinology, 2021)
Introduction: Medullary thyroid carcinoma (MTC) is a rare cancer that accounts for 5% of thyroid cancers. Serum calcitonin is a good biomarker for MTC, which is used for diagnosis, prognosis, and monitoring of recurrence. Calcitonin-negative MTC (CNMTC) is rare but confounds diagnostic and prognostic directions. This study introduces 19 cases of CNMTC in a single center. Method: From 2002 March to 2020 July, more than 76,500 patients had undergone radical thyroidectomy due to thyroid cancer at the Severance Hospital, and a total of 320 patients were diagnosed with MTC (0.4%). Serum calcitonin levels were obtained from every patient who was suspected with MTC. These patients had undergone radical thyroidectomy with central compartment lymph node dissection, and additional modified radical lymph node dissection if lateral lymph node metastasis was positive. Postoperative monitoring and out-patient clinic follow-up were performed with obtaining the serum calcitonin levels. Result: Nineteen patients tested negative for calcitonin preoperatively (6%). The mean preoperative calcitonin level was 5.1 if undetectable level is regarded as 0. Only two patients were males, and the female bias was significant (p = 0.017). No one except two patients with modified radical neck dissection showed central compartment lymph node metastasis. Every patient’s postoperative calcitonin level remained low. There was no recurrence and only one fatality, and the overall survival rate was 95%. Conclusion: Since incidence of CNMTC is not negligible, MTC should not be ruled out in the diagnostic phase even if serum calcitonin is negative in preoperative examination. We presented 19 cases of CNMTC whose prognosis in general were favorable. Markers of serum and immunohistochemical samples other than calcitonin should be actively examined.